A Analysis of the STAD Type Cooperative Learning Model in the Anime Boruto: Naruto Next Generations by Noriyuki Abe - Abdul Gania; Rani Ardesi Pratiwi; Muhammad Iqbal (Global Action and Education for Society, 2026)
The purpose of this study is to analyze the application of the STAD (Student Teams-Achievement Divisions) type of cooperative learning model in the anime Boruto: Naruto Next Generations. The research method uses a qualitative approach with a type of library research. Data collection was carried out using the observation and note-taking technique on dialogues and scenes that represent the five STAD syntaxes equipped with document studies on. Data analysis techniques through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study reveal: (1) The material presentation focused on building positive interdependence , such as team exercises that emphasize